Carbon-silicon-carbon composite fiber, preparation method thereof, negative pole piece, lithium battery and electric device
The preparation of carbon-silicon-carbon composite fibers by two vapor deposition methods solved the problems of low capacity and poor circulation performance caused by Li-Si alloy volume expansion and SEI film generation during the circulation process of lithium-ion batteries, and achieved the effect of significantly improving the circulation performance of the battery.
Patent Information
- Application Number
- CN202311108074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
During the circulation process, traditional lithium-ion batteries with graphite as negative electrodes have low capacity and poor circulation performance due to volume expansion of Li-Si alloy, SEI film generation and active Li loss.
Carbon-silicon carbon-carbon composite fibers were prepared by two vapor deposition methods, and C-Si composite fibers were deposited for the first time, and C-Si-C composite fibers were formed for the second time, which strengthened the conductivity and cyclic properties of the material.
The circulation performance of lithium batteries is significantly improved, and the capacity retention rate after 800 cycles is above 80%, which is better than the commercially available C-Si composite materials.
Smart Images

Figure CN119531122A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a carbon-silicon-carbon composite fiber and a preparation method thereof, as well as a negative electrode sheet, a lithium battery and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in new energy vehicles, smart grids, portable electronic products and other fields. However, lithium-ion batteries with traditional graphite as the negative electrode cannot meet the rapidly growing demand for energy density and cycle performance in various applications. Silicon-based materials are becoming a substitute for commercial graphite or other carbon negative electrode materials due to their low price and high theoretical specific capacity (4200mAh / g). However, during the cycle process, the volume expansion of Li-Si alloy exceeds 300%, and new SEI film will be continuously generated, resulting in a large loss of active Li, and ultimately low battery capacity and poor cycle performance.
[0003] To overcome the volume expansion, electrode pulverization and interface instability problems of silicon-based negative electrode materials, researchers usually adopt the following strategies: (1) size nano-sizing; (2) composite; (3) pre-lithiation. Silicon-carbon composite materials belong to the second strategy, but the carbon-silicon composite materials currently sold on the market are still not satisfactory in terms of the cycle performance of lithium batteries. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a carbon-silicon-carbon composite fiber and a preparation method thereof, so that the carbon-silicon composite fiber can significantly improve the cycle performance of a lithium battery;
[0005] Another object of the present application is to provide a negative electrode sheet, a lithium battery and an electrical device based on the above-mentioned carbon-silicon-carbon composite fiber.
[0006] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a method for preparing a carbon-silicon-carbon composite fiber is provided, comprising:
[0007] Using a mixed gas including protective gas and monosilane to perform a first vapor deposition on cotton to obtain C-Si composite fibers;
[0008] The C-Si composite fiber is subjected to a second vapor deposition using a protective gas carrying a carbon source to obtain a C-Si-C composite fiber.
[0009] Optionally, the volume ratio of the protective gas to monosilane is 95:5-99:1.
[0010] Optionally, the protective gas includes one or more of nitrogen and inert gas.
[0011] Optionally, the first vapor deposition temperature is controlled at 450-800° C. for 1-3 hours.
[0012] Optionally, the second vapor deposition temperature is controlled at 600-800° C. for 1-3 hours.
[0013] Optionally, the carbon source includes a liquid carbon source or a gaseous carbon source.
[0014] As a second aspect of the present application, a carbon-silicon-carbon composite fiber prepared by the preparation method described in the present application is provided.
[0015] As a third aspect of the present application, a negative electrode plate is provided, comprising a conductive agent, a binder, a current collector, and the carbon-silicon-carbon composite fiber described in the present application.
[0016] As a fourth aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode plate, a separator, an electrolyte and the negative electrode plate described in the present application.
[0017] As a fifth aspect of the present application, an electrical device is provided, which uses the lithium-ion battery described in the present application as a power source.
[0018] The present application uses cotton and a carbon source to prepare a carbon-silicon-carbon nanowire composite fiber negative electrode material through two vapor deposition processes. The material preparation process is simple and safe. Compared with conventional silicon-carbon composite materials, it has more significant cycle performance, which provides a new idea for improving the cycle performance and conductive properties of silicon-carbon materials, while reducing the synthesis cost of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Shown is a scanning electron microscope image of the carbon-silicon-carbon composite fiber of Example 1 of the present application;
[0020] Figure 2 Shown is a battery cycle diagram of the carbon-silicon-carbon composite fiber of Example 1 of the present application and a commercially available silicon-carbon composite material. DETAILED DESCRIPTION
[0021] The present application discloses a carbon-silicon-carbon composite fiber and a preparation method thereof, as well as a negative electrode plate, a lithium battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0022] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0023] In the first aspect of the present application, cotton is used as a carrier to derive carbon fibers. Since the density of carbon fibers derived from cotton is large in specific surface area, the specific surface area of the C-Si composite fibers formed by the first vapor deposition also increases (Si particles are attached to the surface of the carbon fibers). The higher specific surface area indicates that due to the support of the carbon fibers, Si can still be well supported without powdering during the cycle. At the same time, the fibrous structure can provide a better flow channel for the current and improve the conductivity of the material.
[0024] After the second vapor deposition, the outer layer of the C-Si composite fiber is carbon-coated to form a C-Si-C nanowire composite fiber structure. The carbon coating layer can reduce the pulverization of Si during the cycle and improve the conductivity of the material.
[0025] Wherein, the method for preparing the carbon-silicon-carbon composite fiber comprises:
[0026] Using a mixed gas including protective gas and monosilane to perform a first vapor deposition on cotton to obtain C-Si composite fibers;
[0027] The C-Si composite fiber is subjected to a second vapor deposition using a protective gas carrying a carbon source to obtain a C-Si-C composite fiber.
[0028] In certain embodiments of the present application, in order to ensure the width and length of the silicon carbon fiber, the present application uses absorbent cotton; in other embodiments of the present application, for the stability of the process, the present application also uses ethanol to wash the absorbent cotton multiple times.
[0029] In certain embodiments of the present application, the volume ratio of the protective gas to monosilane is 95:5-99:1. In other embodiments of the present application, the volume ratio of the protective gas to monosilane is 98:2. Too high a volume ratio will generate a too thin silicon layer, which will reduce the specific capacity of the overall material. Too low a volume ratio will generate an overly thick silicon layer, and the carbon layer generated by the second vapor deposition cannot suppress the volume expansion of silicon, which will reduce the cycle performance.
[0030] In certain embodiments of the present application, the protective gas includes one or more of nitrogen and inert gas, wherein the inert gas includes but is not limited to argon, xenon, helium, radon, etc.
[0031] In certain embodiments of the present application, vapor deposition is performed using a tubular furnace; in other embodiments of the present application, the gas pressure of the tubular furnace is controlled at 1330-3990 Pa, and the gas flow rate is controlled at 20-50 mL / min.
[0032] In certain embodiments of the present application, the first vapor deposition temperature is controlled at 450-800°C, such as 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, and the time is 1-3h, such as 1h, 2h, 3h. The second vapor deposition temperature is controlled at 600-800°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, and the time is 1-3h, such as 1h, 2h, 3h. If the temperature of the two vapor depositions is too high, the reaction will be violent, resulting in uneven deposition, while if the temperature is too low, the reaction will be slow, resulting in a small amount of deposition.
[0033] In certain embodiments of the present application, the carbon source includes a liquid carbon source or a gaseous carbon source. The liquid carbon source includes but is not limited to anhydrous ethanol, benzene, toluene, etc., and the gaseous carbon source includes but is not limited to methane, ethylene, acetylene, etc.;
[0034] In some other embodiments of the present application, a liquid carbon source is used, and the carbon source is carried by a protective gas through a wash bottle into a tubular furnace for a second vapor deposition.
[0035] In the second aspect of the present application, a carbon-silicon-carbon composite fiber prepared by the preparation method described in the present application is provided, and the SEM image is shown in Figure 1 .
[0036] In certain embodiments of the present application, compared with button cells assembled with commercially available C-Si composite materials, button cells assembled with carbon-silicon-carbon composite fibers of the present application have a capacity retention rate of more than 80% after 800 cycles in a comparison of room temperature cycle performance, while the capacity retention rate of button cells assembled with commercially available C-Si composite materials has dropped to about 80% after 300 cycles.
[0037] In the third aspect of the present application, a negative electrode sheet is provided, comprising a conductive agent, a binder, a current collector, and the carbon-silicon-carbon composite fiber described in the present application. The conductive agent, the binder, and the carbon-silicon-carbon composite fiber described in the present application constitute a negative electrode slurry, and the negative electrode sheet is formed by coating the positive electrode slurry on the surface of the current collector.
[0038] In certain embodiments of the present application, the mass percentages of the carbon-silicon-carbon composite fiber, the conductive agent, and the binder in the negative electrode slurry are 90-95:5-2:5-3, respectively.
[0039] In certain embodiments of the present application, the conductive agent is one or more of acetylene black, carbon black, SP, graphite, carbon nanotubes, VGCF, graphene, etc., and the binder is one or more of PVDF, PVP, CMC, SBR, PAA, etc.
[0040] In certain embodiments of the present application, the current collector is a metal foil, such as aluminum foil.
[0041] In a fourth aspect of the present application, a lithium battery is provided, comprising a positive electrode plate, a separator, an electrolyte and the negative electrode plate described in the present application.
[0042] In certain embodiments of the present application, the positive electrode plate is a lithium plate, a conventional polypropylene separator is used as a separator, and lithium hexafluorophosphate is used as an electrolyte to assemble a button half-cell with the prepared negative electrode plate under conditions in a glove box.
[0043] In addition, the lithium-ion battery can also be prepared into various forms of batteries such as soft-pack batteries, half batteries, and full batteries.
[0044] In a fifth aspect of the present application, an electrical device is provided, which uses the lithium-ion battery described in the present application as a power source.
[0045] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0046] The following further describes a carbon-silicon-carbon composite fiber and a preparation method thereof, as well as a negative electrode plate, a lithium battery, and an electrical device provided in the present application.
[0047] Embodiment 1:
[0048] The absorbent cotton was washed several times with ethanol to remove the surface grease;
[0049] Place the cleaned absorbent cotton in a tubular furnace, evacuate and fill with high-purity argon, then fill with argon-monosilane mixed gas (argon:monosilane volume ratio is 98:2), control the flow rate at 20 mL / min, the gas pressure at 1330 Pa, the furnace temperature at 450 °C, and the time for 1 h;
[0050] After completing the above steps, anhydrous ethanol is used as a carbon source, and argon gas is used to bring anhydrous ethanol into a high-temperature tubular furnace through a gas washing bottle. The flow rate is controlled at 20 mL / min, the gas pressure is controlled at 1330 Pa, the temperature in the furnace is 600°C, and the time is 1 hour to obtain the carbon-silicon-carbon composite fiber.
[0051] Embodiment 2:
[0052] The absorbent cotton was washed several times with ethanol to remove the surface grease;
[0053] The cleaned absorbent cotton was placed in a tubular furnace, and after vacuuming, high-purity argon was filled in, and then argon-silane mixed gas (argon: silane volume ratio was 98:2) was filled in, the flow rate was controlled at 50 mL / min, the gas pressure was controlled at 3990 Pa, the furnace temperature was 800 ° C, and the time was 2 h;
[0054] After completing the above steps, anhydrous ethanol is used as a carbon source, and argon gas is used to bring anhydrous ethanol into a high-temperature tubular furnace through a gas washing bottle. The flow rate is controlled at 50 mL / min, the gas pressure is controlled at 3990 Pa, the temperature in the furnace is 800°C, and the time is 2 hours to obtain the carbon-silicon-carbon composite fiber.
[0055] Experimental example:
[0056] The composite material of Example 1 was made into a negative electrode sheet and a commercially available carbon-silicon composite material, which were respectively matched with lithium sheets to make button batteries to test the electrical performance. The cycle performance was tested at room temperature and 0.5°C. The results are shown in FIG. Figure 2 .
[0057] Figure 2It shows that the capacity retention rate of the battery assembled in the present application is above 80% after 800 cycles, while the capacity retention rate of the button-type battery assembled with commercially available C-Si composite materials has dropped to about 80% after 300 cycles, while the capacity retention rate of the battery assembled in the present application is about 87% at this time, which indicates that the carbon-silicon-carbon composite fiber of the present application can significantly improve the cycle performance of the battery.
[0058] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a carbon-silicon-carbon composite fiber, characterized in that: include: Using a mixed gas including protective gas and monosilane to perform a first vapor deposition on cotton to obtain C-Si composite fibers; The C-Si composite fiber is subjected to a second vapor deposition using a protective gas carrying a carbon source to obtain a C-Si-C composite fiber.
2. The preparation method according to claim 1, characterized in that: The volume ratio of the protective gas to monosilane is 95:5-99:
1.
3. The preparation method according to claim 1 or 2, characterized in that: The protective gas includes one or more of nitrogen and inert gas.
4. The preparation method according to claim 1, characterized in that: The first vapor deposition temperature is controlled at 450-800° C. for 1-3 hours.
5. The preparation method according to claim 1, characterized in that: The second vapor deposition temperature is controlled at 600-800° C. for 1-3 hours.
6. The preparation method according to claim 1, characterized in that: The carbon source includes a liquid carbon source or a gaseous carbon source.
7. The carbon-silicon-carbon composite fiber prepared by the preparation method according to any one of claims 1 to 6.
8. A negative electrode plate, characterized in that: It comprises a conductive agent, a binder, a current collector, and the carbon-silicon-carbon composite fiber as claimed in claim 7.
9. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as claimed in claim 8.
10. An electrical device, characterized in that: The lithium ion battery according to claim 9 is used as a power source.